Finding ways to improve orthopedic treatment of patients with complete loss of teeth - Doroshenko Олена Миколаївна; Shepelinskyi Олександр Валерійович (Actual Dentistry, 2023)
Introduction. The effectiveness of complete removable prosthetics remains insufficient. According to WHO (2021), 20.0–26.0% of patients do not use complete removable prostheses. The most common reason for this is unsatisfactory fixation of manufactured structures. During the analysis of the data, it should be noted the tendency towards an annual increase in the number of patients who requested orthopedic treatment of complete absence of teeth during the last two years. It is noted about the better performance of prosthetics with removable prostheses with support on implants, in particular regarding the improvement of their fixation on edentulous jaws. But, despite this, traditional full removable prostheses remain very common due to the economic component of such treatment. Goal: study of age differences in the sensory function of the oral mucosa by testing its stereognostic ability and assessment of the quality of life of patients with complete loss of teeth (on one or both jaws) according to the OHIP-14 (Oral Health Impact Profile) questionnaire. Research methods. Examination of 167 patients with complete loss of teeth included collection of complaints and anamnesis and clinical examination according to the traditional scheme. The type of edentulous upper jaws was determined according to Schroeder, lower jaws according to Kцhler, and the class of the mucous membrane of the prosthetic bed was determined according to Suppli. For oral stereognosis, two varieties of N. Landt’s sets for oral stereognosis were made from "Synma M" plastic in the dental laboratory of the Department of Orthopedic Stomatology of the Shupyk National Healthсare University of Ukraine. The first variety is original, the second variety is geometric shapes, enlarged 8 times. The quality of life of patients was determined using the OHIP-14 questionnaire. The results. The indicators of oral stereognosia are significantly mistaken with increasing age of patients. In young people, in case of tooth loss, the ability to adequately assess the shape and geometric dimensions of solid objects with the help of tactile receptors of the mucous membrane of the oral cavity changes minimally. On all questions of three blocks of the OHIP questionnaire, 14 young and middle-aged patients with complete loss of teeth showed significantly worse indicators than the elderly and senile people and testified to the presence of significant problems related to communication and everyday life, to a lesser extent – eating. On the contrary, the main complaints of the elderly were difficulty in chewing and soreness of the mucous membrane, which is confirmed by the statistical analysis of the material between age groups (p < 0.001). Conclusions. As a prognostic criterion of the adaptation capabilities of patients with full set of teeth, among other research methods, the use of stereognosis data of SOPR is recommended.